Hubungan Kadar Vitamin D dan Gangguan Fungsi Hati pada Pasien Hepatitis B Kronik - Hendri, Sherin Alifia; Arfianti, Arfianti (Jurnal Ilmu Kedokteran, 2021)
Vitamin D plays an important role in the pathogenesis of chronic hepatitis B (CHB) through regulating immune response. This study aimed to determine the relationship between vitamin D levels and impaired liver function in CHB patients. This was an observational analytical study conducted from March to October 2019. We included 36 CHB patients aged 38.31Â±12.98 years and consisted of 16 men and 20 women. Vitamin D levels were measured by enzyme-linked immune assay (ELISA) method while albumin and bilirubin levels were examined by colorimetric assay. Vitamin D levels were in normal limits in 80.6% and insufficiency/deficiency in 19.4% of CHB patients. ALBI ratio scores were good in 75% and moderate-poor in 25% of subjects. Furthermore, there was no significant association between vitamin D levels and the ALBI ratio. In conclusion, this study shows that there is no relationship between plasma vitamin D levels and impaired liver function in CHB patients.